Vortex-induced vibrations of two cylinders with different diameters close to a horizontal plane boundary at low Reynolds number. (1st February 2020) - Janocha, Marek Jan; Ong, Muk Chen; Li, Zhong
Highlights: Near-wall vortex-induced vibrations of two coupled cylinders with different diameters are influenced by the relative position of the small cylinder. In the low Reynolds number regime, placing the small cylinder downstream the large cylinder (a = 0°) and in the position a = 135° extends the lock-in range. When the small cylinder is placed upstream the large cylinder (a = 180°) and in the position a = 45°, the lock-in range is reduced. When the small cylinder is located side-by-side (a = 90°) with the large cylinder, the mean drag and the mean lift force directed towards the bottom plane boundary are increased. Maximum cross-flow vibration amplitude depends on the position angle. Maximum cross-flow vibration amplitude is increased for a = 90° and a = 135° compared to that of a single cylinder. Maximum cross-flow vibration amplitude is reduced for a = 0°, a = 45°, a = 180° compared to that of a single cylinder. Abstract: A numerical study is performed on the vortex-induced vibrations of two rigidly coupled cylinders with different diameters placed in a proximity of a horizontal plane boundary. The two cylinders are elastically supported and free to vibrate in two degrees-of-freedom. The Reynolds number is kept constant at Re = 200 . The influence of the small cylinder placement relative to the large cylinder is systematically studied. The effects on the vibration amplitudes and hydrodynamic forces are analyzed. The flow structures around the cylinders are investigated to elucidate the variations in observed structural responses. At investigated gap ratio ( e / D = 0.9 ), the bottom boundary effects are found to affect the behavior of the structure significantly. The suppression of the vortex shedding from the bottom surface of the large cylinder is observed, leading to in-line vibration lock-in. When the small cylinder is located in the α = 135 ° configuration, the lock-in range is significantly wider than that of a single cylinder configuration. When the small cylinder is located in the α = 90 ° configuration the effect of the small cylinder is manifested by increased mean drag and change in the direction of the mean lift force to negative (directed towards the bottom plane boundary). For the α = 45 ° configuration, reduced vibration response and narrower lock-in range are identified compared with those of the single cylinder, and the other investigated configurations.